Roosting Ecology of the Tent-Roosting Bat Artibeus watsoni (Chiroptera: Phyllostomidae) in Southwestern Costa Rica - Chaverri Echandi, Gloriana (2005)
We described the plants used as roost resources by Artibeus watsoni in southwestern Costa Rica, assessed roost fidelity, and compared roosting ecology between two sites, Golfito and Corcovado, which vary in the degree of human influence. A total of 349 tents from 25 different plant species were used by A. watsoni as roosts; some plant species (e.g., Carludovica palmata, Asplundia alata, Heliconia imbricata and Calathea lutea) were modified into tents with significantly higher frequency than others. The highest tents above the ground were observed in Philodendron popenoei and Rhodospatha wendlandii, whereas tents in Philodendron grandipes and A. alata were significantly lower than any other species. Asplundia alata and R. wendlandii also had the highest frequency of leaves modified per plant. Fidelity of bats to tents was low, although bats used several tents intermittently within a restricted area. Males generally were more faithful to tents than females, although not significantly so. This observation, along with indirect evidence of leaf modification, suggests that males are primarily responsible for tent construction. The two study sites differed in the plants used for roosting and in tent fidelity. Bats in Corcovado used a greater variety of plant species for tent roosting, whereas bats in Golfito were more faithful, suggesting that roosting resources were scarcer at the latter site.